A systematized and chemometrics‐assisted liquid chromatography coupled with tandem mass spectrometry method for quantification of aripiprazole in implantable microparticles in rat plasma from pharmacokinetic study. Issue 9 (7th July 2022) - Rub, Rehan A.; Panda, Sagar Suman; Panda, Sunil K; Almalki, Waleed H.; Alrobaian, Majed; Hafeez, Abdul; Rahman, Mahfoozur; Beg, Sarwar; Ali, Asgar; Ahmed, Farhan J
Abstract: The present research focuses on the systematic development of an analytical method for estimating aripiprazole in rat plasma using ultra‐performance liquid chromatography coupled with tandem mass spectrometry technique. Propranolol was the selected internal standard for this purpose. The reversed‐phase method was developed using ammonium acetate (2 mM) in water containing 0.1% v/v formic acid and acetonitrile with 0.1% v/v formic acid in a ratio of 20:80 v/v as the mobile phase with isocratic elution on an Acquity BEH C18 column (2.1 × 100 mm 2, particle size 1.7 μm). The analyte and internal standard detection were performed under multiple reaction monitoring modes with precursor‐to‐product ion transition with a value of m/z 448.2 → 285.1 for aripiprazole and m/z 260.1 → 116.0 for the internal standard. Method linearity was observed in a concentration ranging between 0.1 and 50 ng/ml with a correlation coefficient of 0.9999, while a lower limit of quantification was observed at 0.1 ng/ml. The robustness was optimized with the mapping of the influential variables by experimental design for maximum recovery of drug from rat plasma during the pharmacokinetic evaluation of aripiprazole after intramuscular administration of microparticles.